A decentralized application for logistics: Using blockchain in real-world applications - Andreou, Andreas S.; Christodoulou, Panayiotis; Christodoulou, Klitos (My University, 2018)
A prototypical smart contract (wrapped as a decentralized application) is presented for investigating the potential benefits for applying Blockchain for Logistics. The decentralized application proposed exposes the various design challenges that programmers are likely to face when realizing the implementation of the application. The proposed methodolog y utilises the implementation of a dedicated smart contract that was developed based on a special-purpose structure for satisfying the requirements of the usecase. The evaluation was based on the execution of each of the functions measuring the gas costs and execution time. The prototype design was deployed and evaluated on a real-world Blockchain framework and can be considered as a first solution to how the Blockchain technolog y can be utilized within Logistics to overcome any barriers that may exist between professionals. In this paper we present a real implementation of a smart contract for the Logistics industry. The proposed dApp provides a live example of how Blockchain can be utilized within Logistics as it enables users to send and track products.
Keywords: Smart contracts; Blockchain; Decentralized applications; Decentralized logistics